Chemical process control : an introduction to theory and practice - Stephanopoulos, George (Prentice Hall, 1984)
The control of a chemical process: its characteristics and associated problems;Modeling the dynamic and static behavior of chemical processes;Analysis of the dynamic behavior of chemical processes;Analysis and design of feedback control systems;Analysis and design of advanced control systems;Design of control systems for multivariable processes: introduction to plan control;Process control using digital computers.